Analisis Faktor-Faktor yang Mempengaruhi Niat Beli Produk Halal di Indonesia - Frida Nisrina Aulia; Hendri Hermawan Adinugraha; Drajat Setiawan (TSARWAH, 2023)
This study aims to analyze the factors that influence the intention to buy halal products in Indonesia. As a country with the largest Muslim population in the world, Indonesia is a significant market for halal products. Understanding the factors that drive consumer intentions to buy Halal products is very important for business people and policymakers to meet the increasing demand for Halal products in this country. This study uses a literature review method with a qualitative approach. The findings from this study will provide a comprehensive understanding of the factors that shape consumer attitudes and behavior towards halal products. The results of the study show that there are 4 factors that can be analyzed in the decision to purchase food products labeled halal, namely 1) the religious factor, this factor is the most important factor, but besides being halal the food is also tayyib, not redundant, and brings benefit. 2) psychological factors, namely Indonesian people feel worried about the non-halalness of a product even though it has a halal logo printed on it, so they pay attention to the ingredients contained in the packaging. 3) social factors, is driven by reference groups, family, and also the role of the clergy in the local area. 4) cultural factors, namely because Islam is synonymous with local culture, people sometimes join in buying a product, without paying attention to the halal label.